Does supplementation of vitamin C, reduced glutathione or their association in semen extender reduce oxidative stress in bovine frozen semen? - Pinto,S.C.C. (2020)
ABSTRACT The aim of this study was to evaluate the addition of vitamin C, reduced glutathione and the association thereof to the bovine semen cryopreservation extender. The ejaculate from nine bulls were divided into four fractions, each corresponding to a treatment, namely: control group-semen diluted with Tris-yolk extender; vitamin C group-semen diluted in Tris-yolk extender supplemented with vitamin C (2.5mmol/mL); glutathione group-semen diluted in Tris-yolk extender supplemented with reduced glutathione (2.5mmol/mL) and associated group-semen diluted in Tris-yolk extender supplemented with vitamin C (1.25mmol/mL) and reduced glutathione (1.25mmol/mL). Afterwards, the semen was packed into French straws and submitted to cryopreservation using automated equipment. After cryopreservation, the semen was thawed and evaluated considering sperm motility, morphology, plasma membrane, acrosome, mitochondrial potential and oxidative stress, as well as the thermo resistance test. Extender’s supplementation with the association of vitamin C and reduced glutathione showed benefic effects on sperm motility and preservation of plasma and acrosomal membranes during semen cryopreservation, being also the group that showed higher values of reactive oxygen species. Thus, the association of both antioxidants contributed to the preservation of sperm cells in every analyzed characteristic, suggesting its use on bovine semen cryopreservation.